Antihistamines in the treatment of allergic diseases: not as simple as it seems! - Igor S. Guschin; Oksana M. Kurbacheva; P.S. Osipova (LLC "MEDIAFORMAT", 2023)
According to WHO, up to 35% of the world's population suffers from allergic diseases, and this number is growing exponentially. Histamine has been proven to play a key physiological role in the pathogenesis of allergic disorders by affecting tissues through the activation of H1-receptors. H1-antagonists (antihistamines) are widely used to treat allergic disorders, being one of the most prescribed classes of drugs. The development of medications with high specific activity and low incidence of unwanted side effects is the main goal of pharmaceutical research, so antihistamines have evolved significantly since their first generation was introduced more than 50 years ago. This review analyzes aspects of classification and concepts of clinical use of antihistamines considering their individual specificity.